The psychophysiological differences between expert and novice rifle shooters during the aiming period - Yildiz, M.; Fidan, U. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Purpose: Determination of mental status of the rifle shooters during the shooting performance is critical for the development of mental training programs according to their skill levels. The purpose of this study was to investigate the psychophysiological differences of expert and novice rifle shooters. Material: Fourteen expert (age: 28.08±9.12 years, height: 176.12±4.24 cm, weight: 73.56±5.28 kg) and twenty novice shooters (age: 21.08±3.12 years, height: 177.42±3.74 cm, and weight: 71.56±3.57 kg) participated in the current study. The participants performed five shootings from a distance of 10m. The averages of each shooter`s five shooting scores, values of attention and meditation, and heart rate between 5-sec before shooting and shooting moment were obtained. Results: It was determined that shooting scores (10.02 ±0.49 vs. 7.6±2.86, p<0.01, respectively) and meditation level (71.50±21.05 vs. 52.93±20.54, p<0.05, respectively) were significantly higher in the experts while attention level (73.63±21.11 vs. 59.76±21.26, p<0.05, respectively), and heart rate (105.34±12.12 vs. 98.67±7,12 bpm, p<0.05, respectively) were found higher in the novices. Conclusions: The novices and experts present different psychophysiological responses during the aiming period. It is suggested that the psychophysiological differences can be useful to categorize shooters and to provide feedback in training because it is important to develop programs according to group levels, especially in the development of mental training programs. Besides, it is determined that the mobile EEG device is an effective method for determining the mental status of athletes in sports specific activities.